Optimalisasi Layanan Bimbingan dan Konseling Melalui Sistem Informasi Berbasis Website di Institusi Pendidikan - Rizki Amalia Kaimudin; Rafael Lisinius Ginting (Jurnal Tematik, 2026)
This study aims to optimize guidance and counseling services through the development of a web-based information system at Universitas Negeri Medan. The system is designed to be flexibly accessible to students and to facilitate service management by the Counseling and Guidance Unit. The development process adopted the 4D model (Define, Design, Develop, and Disseminate), resulting in a website featuring the homepage, about us, services, articles, and contact pages. The system was evaluated by material experts, media experts, and students based on aspects such as content design, language, usability, utility, and visual design. The results show that the system obtained scores of 80.15% from media experts, 84.21% from students, and an overall effectiveness level of 93.18%, all categorized as “excellent.” These findings indicate that the developed web-based guidance and counseling information system is effective, feasible, and has the potential to improve the quality and efficiency of counseling services in higher education institutions.